2010
DOI: 10.1158/1535-7163.mct-10-0172
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Administration of Polymeric Nanoparticle-Encapsulated Curcumin (NanoCurc) Blocks Tumor Growth and Metastases in Preclinical Models of Pancreatic Cancer

Abstract: Curcumin or diferuloylmethane is a yellow polyphenol extracted from the rhizome of turmeric (Curcuma longa). A large volume (several hundreds) of published reports has established the anticancer and chemopreventative properties of curcumin in preclinical models of every known major cancer type. Nevertheless, the clinical translation of curcumin has been significantly hampered due to its poor systemic bioavailability, which mandates that patients consume up to 8 to 10 g of the free drug orally each day to achie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
134
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(142 citation statements)
references
References 44 publications
7
134
0
1
Order By: Relevance
“…In vivo studies of PLGA and polyNI-PAM nanogel curcumin formulations have shown improved bioavailability, and therefore are more effective systems for delivering curcumin into tumors. 12,14,16,72,73 These data clearly support the overall conclusion of this study. Our future research efforts will include evaluation of the in vivo pharmacokinetics of these curcumin nanoformulations to clarify the underlying mechanisms for potential cancer therapeutics.…”
supporting
confidence: 90%
“…In vivo studies of PLGA and polyNI-PAM nanogel curcumin formulations have shown improved bioavailability, and therefore are more effective systems for delivering curcumin into tumors. 12,14,16,72,73 These data clearly support the overall conclusion of this study. Our future research efforts will include evaluation of the in vivo pharmacokinetics of these curcumin nanoformulations to clarify the underlying mechanisms for potential cancer therapeutics.…”
supporting
confidence: 90%
“…The association with CP is also useful for ovarian cancer treatment (Yallapu et al, 2010b), while in vivo studies proved the synergism of CUR nanoformulation prepared by free radical polymerization of NIPAAm, VP, and AA with Gemcitabine in Pa03C Xenograft mouse model (Bisht et al, 2010).…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%
“…The CRT expression on the cell surfaces of the B 16 cells was evaluated using the anti-CRT antibody (Bisht et al, 2010). Tumor sections on the silane-coated slides were deparaffinized with xylene and dehydrated with ethanol.…”
Section: Immunohistochemistrymentioning
confidence: 99%